Characteristics of Hysterosalphingography Findings in Infertile Patients at Prof. Dr. I.G.N.G Ngoerah Central Hospital at Periode of January 2021 to June 2024 - Firman Parulian Sitanggang; Putu Patriawan; Regina Primeylisa Dos Santos; Agnes Caroline; Gandis Ayu Wardani (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2024)
Introduction: Infertility is the inability to achieve pregnancy after 12 months of regular unprotected intercourse, affecting millions globally. In Indonesia, it affects 10-15% of reproductive-aged couples. Infertility can be classified as primary (no prior pregnancies) or secondary (previous pregnancies). HSG is commonly used to assess uterine and tubal abnormalities, key contributors to infertility. Methodes: Descriptive qualitative study are done to examine correlation of age, uterine abnormalities, and fallopian tube abnormalities from HSG findings with the prevalence of infertility from patients in Radiology Department from Prof. Dr. I.G.N.G. Ngoerah Central General Hospital, covering the period from January 2021 to June 2024.Results: 66 patients were collected as samples. 47 patients (71.21%) have primary infertility, while 19 patients (28.79%) have secondary infertility. 9 patients (13.63%) have uterus abnormalities, while 21 patients (31.81%) have fallopian tube abnormalities.Discussion: Hysterosalpingography (HSG) is a key diagnostic tool in evaluating infertile patients, providing insights into uterine and fallopian tube morphology and patency. It detects structural abnormalities like retroflexed uterus, didelphys, or blocked tubes, which can hinder sperm-egg interaction, embryo implantation, or cause recurrent miscarriages, affecting fertility. Keywords: Abnormalities, Fallopian tube, Hysterosalphyngography, Infertiliy, uterus